2017
DOI: 10.1007/978-3-319-56282-7
|View full text |Cite
|
Sign up to set email alerts
|

Political and Religious Identities of British Evangelicals

Abstract: of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Sandra's view that Christian leaders should not interfere with politics follows HTB leaders' pattern of abstaining from political commentary in church. Her view also supports a study that reports evangelicals find it "decidedly 'un-British'" to be preaching politics from the pulpit (Hatcher 2017b). This finding, and the way HTB congregants reacted to their leaders' silence, suggest that, prior to Brexit, to be a British evangelical meant to support a separation between church and party politics.…”
Section: The Role Of Christian Leaders In Politicssupporting
confidence: 68%
See 1 more Smart Citation
“…Sandra's view that Christian leaders should not interfere with politics follows HTB leaders' pattern of abstaining from political commentary in church. Her view also supports a study that reports evangelicals find it "decidedly 'un-British'" to be preaching politics from the pulpit (Hatcher 2017b). This finding, and the way HTB congregants reacted to their leaders' silence, suggest that, prior to Brexit, to be a British evangelical meant to support a separation between church and party politics.…”
Section: The Role Of Christian Leaders In Politicssupporting
confidence: 68%
“…Evangelicals have an internationalist outlook and are politically mobilised around issues more than party affiliation in Britain. Moreover, white British evangelicals themselves do not desire a political impact in the way that most white American evangelicals do (Hatcher 2017b;Strhan 2015). Given the significant role of religion, particularly Anglicanism, in the referendum, and the impact of Brexit for years to come, it is crucial that further qualitative research investigates how Christian identities continue to change in relation to political events.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified the most important religious interest groups in the US, especially those active in Washington DC (Hertzke 1988;Hofrenning 1995;Knutson 2011;Pew Forum on Religion and Public Life 2012). In the UK, while scholars have analyzed key individual organizations or policy episodes (e.g., Steven 2011), and their grassroots supporters (Hatcher 2017), the most comprehensive effort to map the sector and its priorities focused on a specific subset: socially conservative "Christian Right" campaign groups (Kettell 2016a). Thus far, however, there has been no comparable academic analysis of the UK Christian interest group sector as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Closely connected to the type of organization is their issue agendas-that is, the policy issues on which they attempt influence. Much of the existing research into UK Christian interest groups has focused on traditional "moral" issues such as embryology and same-sex marriage (Kettell 2010(Kettell , 2019)-yet among the grassroots, even the UK's evangelical constituency has much wider concerns (Hatcher 2017). While there has been some consideration of more mainstream issues (Kettell 2013a), the extent to which these are prioritized by the sector as a whole is less clear.…”
Section: Introductionmentioning
confidence: 99%